PENGELOLAAN AGROFORESTRI DUSUNG BERBASIS PALA (Myristica fragrans, Houtt) DI NEGERI SEITH KECAMATAN LEIHITU KABUPATEN MALUKU TENGAH - Tanasi, Rohani Rahmawati; Hatulesila, Jan Willem; Wattimena, Cornelia M. A. (PT. BARRINGTONIA ASIATICA LESTARI, 2025)
Agroforestry management plays a crucial role in ensuring the sustainability of the dusung system by supporting both the local economy and environmental conservation. This study aims to examine the management of nutmeg-based agroforestry and to analyze the economic value of the dusung agroforestry farming system as a source of household income for farmers. A descriptive-exploratory method with a non-experimental approach was used, employing data collection techniques such as observation, interviews, questionnaires, literature review, and documentation. The data were analyzed descriptively through tabulation and interpretation, in line with the objectives of the study. The results show that dusung management is carried out hereditarily by farming families using a mixed cropping system that combines nutmeg with other crops on the same plot of land. Maintenance, harvesting, and post-harvest processing activities are conducted independently and still rely on local knowledge. This management model reflects a form of traditional agroforestry that is adaptive to the social and ecological conditions of the community.